Dissipative elastic metamaterials for broadband wave mitigation at subwavelength scale. (February 2016) - Chen, Y.Y.; Barnhart, M.V.; Chen, J.K.; Hu, G.K.; Sun, C.T.; Huang, G.L.
Abstract: In this paper, an elastic metamaterial with multiple dissipative resonators is presented for broadband wave mitigation by properly utilizing interactions from resonant motions and viscoelastic effects of the constitutive material. The working mechanism of the metamaterial to suppress broadband waves is clearly revealed in a dissipative mass-in-mass lattice system through both negative effective mass density and effective metadamping coefficient. Based on the novel metadamping mechanism, a microstructure design of the dissipative metamaterial made of multi-layered viscoelastic continuum media is first proposed for efficient attenuation of a transient blast wave. It is found that the extremely broadband waves can be almost completely mitigated with metamaterials at subwavelength scale. The results of the study could be used in developing new multifunctional composite materials to suppress the shock or blast waves which may cause severe local damage to engineering structures.